Protective effects of ginsenoside CK against oxidative stress-induced neuronal damage, assessed with 1H-NMR-based metabolomics - Na Li; Yanhong Zhang; Jingwei Lv; Dazhong Sun; Jianan Lin; Qihang Pang; Hui Li; Zhanhong Cao; Yaxin Liu; Zhen Li; Xingyu Fang; Dianyu Li; et al. (Compuscript Ltd, 2022)
Oxidative stress is an important pathogenic mechanism in degenerative diseases such as Alzheimer's disease. Although ginsenoside compound K (CK) is protective against neuronal oxidative damage, the underlying mechanism remains to be understood. In this study, the protective effects of ginsenoside CK against oxidative stress damage induced by hydrogen peroxide in HT22 cells were investigated with 1H nuclear magnetic resonance (1H-NMR)-based metabolomics. The optimal CK concentration for decreasing oxidative stress damage in nerves was determined with MTT assays. CK (8 μM) significantly increased the HT22 cell survival rate after the model was established. Cell lysates were subjected to 1H-NMR metabolomics, western blotting, and ATP assays for verification. Metabolic perturbation occurred in HT22 cells in the model group but not the control group. Twenty biomarkers were identified and used to analyze metabolic pathways. CK reversed metabolic changes in HT22 cells by altering taurine, glutamate, glycine, and glutathione metabolism. Subsequently, CK increased ATP content and the expression of components of the PI3K/AKT signaling pathway in HT22 cells. These findings demonstrated that CK prevents oxidative stress damage and protects nerves by regulating energy-metabolism pathways, such as those of taurine, glutamate, and other amino acids, thus providing a rationale for the use of CK in Alzheimer's disease treatment.